2022
DOI: 10.1089/vio.2021.0032
|View full text |Cite
|
Sign up to set email alerts
|

Feminicide Violence Before and During the COVID-19 Health Emergency

Abstract: This work explores the extreme violence against women before and during the COVID-19 pandemic in Peru, considering different restriction periods. This is relevant in view of increased violence against women. The objective of this work was to identify the feminicide and attempted feminicide during different quarantine periods due to the COVID-19 health emergency in Peru, and to determine the variables related to these. Data of administrative records of the cases of feminicide and attempted feminicide were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In a similar study conducted in Peru that described the attempted femicide and femicide cases during pre-quarantine, quarantine, and restrictive-measures periods during the COVID-19 pandemic in 2020, there was a significantly higher proportion of fatal cases during the quarantine period (32.6%) compared with the other periods (pre-quarantine: 19.9% and restrictive measures: 22.0%). Similar to our findings, the attempted-femicide risk in Peru increased with antecedents of physical and psychological violence (i.e., previous legal complaints), as well as living in urban areas during the three scenarios [39].…”
Section: Discussionsupporting
confidence: 88%
“…In a similar study conducted in Peru that described the attempted femicide and femicide cases during pre-quarantine, quarantine, and restrictive-measures periods during the COVID-19 pandemic in 2020, there was a significantly higher proportion of fatal cases during the quarantine period (32.6%) compared with the other periods (pre-quarantine: 19.9% and restrictive measures: 22.0%). Similar to our findings, the attempted-femicide risk in Peru increased with antecedents of physical and psychological violence (i.e., previous legal complaints), as well as living in urban areas during the three scenarios [39].…”
Section: Discussionsupporting
confidence: 88%
“…In Peru, the trend of homicides involving women followed a U-shape: femicides decreased during the first weeks of the pandemic and then rebounded (Calderon-Anyosa et al, 2021). A different study on Peru (Bardales Mendoza et al, 2022) and a study on Chile (Cantor et al, 2022) showed an increase in the number of attempted femicides during the quarantine period. The same Chilean study also observed a stability in the number of femicides before and during the pandemic period, with a reduction of cases in places with higher socioeconomic conditions (Cantor et al, 2022).…”
Section: The Impact Of Covid-19 On Femicides: a Review Of The Literaturementioning
confidence: 95%
“…During the COVID-19 pandemic, targeted populations, such as people of color, people with disabilities, and women experienced heightened levels of precarity and violence (Bardales Mendoza et al, 2021;Cetina, 2021;Perry et al, 2021;Weil, 2020) Militarized quarantine in countries of the global south (Collantes, 2021;Molina Aguilar & López, 2021) made it almost impossible to continue with traditional activist strategies, such as protests and inperson meetings. The new pandemic dynamic changed and disrupted the modus operandi of social movements (Bao, 2020;Mendes, 2020;Pleyers, 2020).…”
Section: Covid-19 Abortion Legislation and The Emergence Of Las Femid...mentioning
confidence: 99%